Evaluation of Inclusive Elementary School Learning in Yogyakarta - Windi Widyastuti; Haryanto Haryanto (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to evaluate inclusive school learning at inclusive elementary schools in Yogyakarta. This is an evaluative study using the discrepancy evaluation model by Malcolm Provus  through 5 steps of evaluation (design, installation, process, measurement, and comparison) to classify constructs in research papers. Data collection techniques using observation, interviews, and documentation. The validity of the data is done through data triangulation. The evaluation uses a discrepancy evaluation model. The results showed that: 1) inclusive school learning planning in this school used a curriculum and RPI tailored to students' needs. So that the evaluation of the implementation of the curriculum and RPI follows the practice of curriculum planning at other inclusive schools, 2) the implementation of inclusive school learning, which includes the application of teaching strategies, and inclusive student learning assistance, there are no gaps by the practice of curriculum planning at other inclusive schools., 3) there is no gap in the assessment of inclusive school learning following curriculum planning practices at other inclusive schools because the comparison is based on procedures that have been carried out at other inclusive schools.